Quality Assurance in Homoeopathic Pharmaceuticals - Role of NABL Accreditation of Laboratories (Homoeopathy for All, 2024)
Homoeopathic Pharmacy has its  own distinct presence attributable  to its specific techniques of  preparation. Since its development  homoeopathic pharmacy has  embraced the latest technological  advances and utilised them for  improving drug manufacturing  while remaining true to the  core process of homoeopathic  potentistation as established  by Dr Hahnemann. Increasing  popularity of homoeopathy has  lead to simultaneous increase in  requirement of medicines.  Dr Hahnemann repeatedly  asserted on need of genuine good  quality medicine. His focus on  good quality raw materials and  strict observance of preparation  techniques is evident in his writings.  Development of pharmacopeias  further strengthened standardization  in homoeopathic pharmacy.
Keywords: Homoeopathic; pharmacopeias; pharmacy